Dante's Analogy between 'Philosophy' and 'Friendship' in Convivio III, xi (Doctor Virtualis, 2023)
The article focuses on the analysis of the extended comparison between philosophy and friendship advanced by Dante in Convivio III, xi, interpreting it as a conscious analogy. Starting from a careful exegesis of the chapter, read as Dante’s peculiar accessus ad philosophiam, the article goes through the stages of the analogy, and it highlights its main theoretical contents. In this way, it becomes possible to show the relevance of the topic of friendship (especially that between master and student) for a correct understanding of one of the fundamental (and most debated) aspects of philosophical practice as conceived by Dante, i.e., its intrinsically collective character. Moreover, the article underlines that friendship constitutes for Dante one of the essential instruments in order to broaden philosophical knowledge outside of university circles, something that the Convivio explicitly purports to do.
Keywords: Dante; Convivio; Analogy; Philosophy; Friendship